Structure of the voltage-dependent potassium channel is highly conserved from Drosophila to vertebrate central nervous systems. - Baumann, A (1988)
Voltage-sensitive potassium channels are found in vertebrate and invertebrate central nervous systems. We have isolated a rat brain cDNA by cross-hybridization with a probe of the Drosophila Shaker gene complex. Structural conservation of domains of the deduced protein indicate that the rat brain cDNA encodes a voltage-sensitive potassium channel. Of the deduced amino acid sequence, 82% is homologous to the Drosophila Shaker protein indicating that voltage-sensitive potassium channels have been highly conserved during evolution. Selective pressure was highest on sequences facing the intracellular side and on proposed transmembrane segments S4-S6, suggesting that these domains are crucial for voltage-dependent potassium channel function. The corresponding rat mRNA apparently belongs to a family of mRNA molecules which are preferentially expressed in the central nervous system.